Simultaneous seismic inversion for fluid indicator and brittleness index in the gas-bearing shale reservoir - Li, Chenlong; Wen, Xiaotao; Zhao, Yun; Li, Bo; Zhang, Yuqiang (Frontiers in Earth Science, 2025)
Accurate estimation of brittleness index, characterizing the brittleness level of rocks, and reservoir fluid identification are crucial for the characterization and development of shale gas reservoirs. However, conventional seismic methods for the sweet spot parameters failed to realize the simultaneous inversion of fluid indicator and brittleness index, challenging exploration of the favorable fracturing areas for shale gas production. For this issue, we concentrate on the simultaneous seismic inversion method of fluid indicator and brittleness index. First, we have derived a novel PP-wave reflection coefficient equation incorporating the above sweet spot parameters, allowing the direct estimation of reservoir brittleness and fluid properties. Two groups of classical layered medium models are introduced to justify the high accuracy of the novel equation within the incidence angle of 40°. Then, to effectively decouple these parameters from the pre-stack seismic data, anisotropic total variation based on LP norm sparse constraint (ATpV) seismic inversion method is introduced to obtain accurate inversion results, extracting sparser priori information through the strong sparsity of the LP norm. Numerical model examples demonstrate the high stability and robustness of the proposed simultaneous inversion method. Ultimately, we applied it to field seismic data from a gas-bearing shale reservoir in the Sichuan Basin, China. A comprehensive analysis of the three-dimensional (3D) inversion results with logging, geological structure, and micro-seismic events detected from horizontal fracturing wells has validated the rationality of the method.